A Review of Applied Theories in Studies of Knowledge Sharing Behavior - Fatemeh Hamidi; Fatemeh Nooshinfard (بازیابی دانش و نظام‌های معنایی, 2019)
Abstract This article aimed to have a deep understanding of knowledge sharing behavior as a key element in the knowledge management process and the survival factor of organizations in the present era and tried to illustrate this point by analyzing applied theories in this field and to show how these theories have facilitated distinctive research on knowledge sharing. The present article is a narrative review and uses a library method to study a variety of articles that examine the motivational factors affecting knowledge sharing behavior in and out of the country, based on different theories. After extracting the theories from related articles, it became clear which of these theories belong to which disciplines and their applicability in this field was identified.Various motivational factors that influence individuals to engage in knowledge sharing behavior are examined by analyzing the theories in the fields of social psychology, economics, knowledge and information science and management that have been used in studies of this field.  It is found that theory of reasoned action, theory of planned behavior, Social exchange theory, balance theory, self-determination theory, costly signaling theory and regulatory focus theory from social psychology, resource dependency theory in economics, anomalous State of knowledge theory from knowledge and information science and organizational climate theory from management are applicable in the area of knowledge sharing behavior. In order to interpret the knowledge sharing behavior, it was necessary to analyze the theories applied and adopted from other disciplines in this field to provide a deep insight into the psychological, economic, organizational, as well as individual capabilities that influence the intentions of individuals to share knowledge. Knowledge sharing can gain much of its understanding of theories of social psychology. Concepts such as the attitude and behavioral intention of these theories affect knowledge sharing behavior.By understanding the recurrent relationships between different organizational and individual motivational factors, knowledge sharing behaviors and outcomes can understand how organizations can adapt knowledge sharing processes to performance improvement. Senior executives should pay serious attention to, and support, in providing facilities, building trust, encouraging and educating employees about sharing knowledge and its benefits.